2018
DOI: 10.1111/ctr.13408
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for individuals turned down for living kidney donation

Abstract: Generic instruments measuring quality of life, depression, financial stress, and provider empathy revealed no significant differences between kidney donors and turned-down donors. However, qualitative interviews revealed preliminary evidence that some turned-down donors experienced emotional consequences. These findings warrant confirmation in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
4
21
1
Order By: Relevance
“…They felt they were denied autonomy or perceived inconsistencies or unfairness in the eligibility criteria. A recent study on outcomes of individuals turned down for living kidney donation also found that ineligible donor candidates felt a sense of lost autonomy, however the externalization of ‘blame’ and anger directed towards the transplant team is a novel finding from our study. Ineligible donor candidates whose intended recipient had other potential living kidney donors, or who had since received a transplant, found it easier to accept the clinical decision and understand that donating their kidney may pose significant medical risks to themselves and/or the recipient.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…They felt they were denied autonomy or perceived inconsistencies or unfairness in the eligibility criteria. A recent study on outcomes of individuals turned down for living kidney donation also found that ineligible donor candidates felt a sense of lost autonomy, however the externalization of ‘blame’ and anger directed towards the transplant team is a novel finding from our study. Ineligible donor candidates whose intended recipient had other potential living kidney donors, or who had since received a transplant, found it easier to accept the clinical decision and understand that donating their kidney may pose significant medical risks to themselves and/or the recipient.…”
Section: Discussionsupporting
confidence: 47%
“…There is ongoing debate about the extent to which the donor‐recipient relationship should alter the level of acceptable risk to the donor. The emphasis on autonomy expressed by some parent and spousal ineligible donor candidates in our study has also been articulated in a recent study of ineligible donor candidates as well as studies conducted in living donors and among the general community . The current KDIGO guidelines recommends the assessment of benefits and risks to the potential donor, however, there is no consensus on the maximum level of acceptable risk and quantification of the potential emotional and psychological benefits is complex Further, there has been a recent shift from considering the risks to the donor and benefits to the recipient at an individual level, toward a decision‐making model that combines risks and benefits for ‘interdependent donors’ (donors residing in the same household as their recipient), particularly in liver donation where recipient death is imminent without a transplant .…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations